2013
DOI: 10.1016/j.cegh.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective case study of clinical profile of hospitalized children with type 1 diabetes mellitus at a tertiary health care center in northern India

Abstract: Background: Type 1 diabetes mellitus (T1DM) mostly presents as diabetic ketoacidosis (DKA) and is a common pediatric endocrine emergency. There is dearth of literature on clinical profile of T1DM from North India. Objectives: 1. To identify the clinical profile of patients admitted with T1DM at a tertiary care hospital. 2. To assess the predictors of adverse outcome in patients with T1DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
10
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 7 publications
6
10
3
Order By: Relevance
“…6 The mean age at presentation in our series was 7.96 year+ 3.63. This is in agreement with other studies from India, that by Durga Prasad et al 7 (mean age + SD 8.12 + 3.7). In the current study, it was observed that majority of the study population (71.76%) were above 5 years of age and only 28.24% in 0-5 years age group.…”
Section: Discussionsupporting
confidence: 94%
“…6 The mean age at presentation in our series was 7.96 year+ 3.63. This is in agreement with other studies from India, that by Durga Prasad et al 7 (mean age + SD 8.12 + 3.7). In the current study, it was observed that majority of the study population (71.76%) were above 5 years of age and only 28.24% in 0-5 years age group.…”
Section: Discussionsupporting
confidence: 94%
“…8 Other research conducted at King George's Medical University Hospital, India showed that pediatric patients with type 1 diabetes mellitus who suffered from diabetic ketoacidosis, commonly suffered from hyponatremia. 9 However, in this study, hypernatremia patients were dominated by a diagnosis of acute diarrhea severe dehydration. These results are different from research conducted at M. Djamil Academic Hospital Padang, acute diarrhea with severe dehydration in pediatric patients showed that the most electrolyte disorders experienced was hyponatremia.…”
Section: Demographic Profile Of Patientsmentioning
confidence: 58%
“…In contrast to this, other studies showed a slightly upward trend in the severity of DKA. 15,[18][19][20] Data from our study has shown that there is no significant association between the severity of ketoacidosis and the demographic variables like age, gender, socioeconomic status and family history of diabetes. This is supported by report from other studies.…”
Section: Graph 1 Profile Of Symptomsmentioning
confidence: 91%